THE INFLUENCE OF FINANCIAL PERFORMANCE TOWARDS FOOD SUBSTRATE MANUFACTURING COMPANY'S RETURNBEVERAGES IN THE PACKAGES ARE EXISTING AND REGISTERED IN INDONESIA STOCK EXCHANGE PERIOD OF 2013-2017 - Sipayung, Monita Herawaty; Tarigan, Lukas (Fundamental Management Journal, 2020)
He problem of the main objective of investors to invest their funds in the capital market is, among others, to get a maximum return on certain risks. Investors are interested in stocks that have positive and high returns because they will improve the welfare of investors. To attract investors, companies and improve their financial performance. Measurement of financial on thee performance can be done using financial ratios. so in this case if the financial performance of a company is good, it will automatically also affect the stock price movements in the capital market. As study To determine whether the measured financial performance is through the financial ratios of Gros Profit Margin (GPM) Earning Per Share (EPS), Debit to Equity Ratio (DER), Return on Equity (ROE), Return on Assets ( ROA) has a significant effect on stock returns. there is also a method that is used in this fixing is Addit Market Value (MVA) analysis, t test analysis and also F test is used by a sample of 8 companies through purposive sampling method. The results obtained in this study prove that the MVA analysis proves that the company's development moves simultaneously and is seen partially only Gros Profit Margin (GPM), which affects the Stock Return, but if viewed simultaneously addressing the four variables that affect significant to Stock Returns. Keywords: Gros Profit Margin , Earning Per Share, Debit to Equity Ratio, Return on Equity, Return on Asset